Minimization of Transactional Overhead Size in Data Storing Process in Carrotspot Motivation Platform with Use of Blockchain Technology: Case Study - Grzegorz BLIŹNIUK; Arkadiusz SZCZEBIOT; Aleksander SURMAN (Communications of International Proceedings, 2021)
In R&D project no. POIR.01.01.01-00-1011/18, granted by Poland’s NCBiR institution, we were testing different approaches to effective and safe storage of history of granting recognitions awards between employees in companies. That was very important for us regarding expected huge scale of frequency of awards transactions. Initially we wanted to store all of  the awards as “tokens” implemented using smart contracts shared by blockchain technology – our final choice was Hyperledger Fabric technology.  In this paper we described main considerations and observations about usage of Hyperledger Fabric, Quorum, Ethereum and R3 Corda technology in our issue. That was an interesting topic, because influenced by our conclusions from researches, we changed our previous assumptions for the method of implementing history of incentive awards to employees and scope of effective use of smart contracts implemented by blockchain technology. Our key finding was to big transactions overhead in relation of our requirements in smart contracts storing. This conclusion was result of our experimental testing of selected blockchain technologies pointed in article. In details, regarding conclusions of our researches, we rejected our first idea of using blockchain smart contract for storing of all tokens transactions . That was crucial analytical decision for us, because in this case only traditional database technology was -and still is - fully useful for us. More details in contents of paper.
Keywords: Blockchain; IT Systems; HR Technology.